COCONUT STEM UTILIZATION IN SRI LANKA - Ranjith Mahindapala (International Coconut Community Journal, 1989)
In the plantation agriculture in Sri Lanka, coconut occupies the highest area of nearly 420,000 ha. It is distributed in all 24 districts. The estate sector (8 ha or more) comprises 104,000 ha (24.7%) of the area while the balance, 316,000 ha (75.3%) is categorized as small holdings